MALDI Imaging Analysis of Neuropeptides in the Africanized Honeybee (Apis mellifera) Brain: Effect of Ontogeny - Pratavieira, Marcel [UNESP]; Silva Menegasso, Anally Ribeiro da [UNESP]; Caviquioli Garcia, Ana Maria [UNESP]; Santos, Diego Simoes dos [UNESP]; Gomes, Paulo Cesar [UNESP]; Malaspina, Osmar [UNESP]; Palma, Mario Sergio [UNESP] (Amer Chemical Soc, 2014)
The occurrence and spatial distribution of the neuropeptides AmTRP-5 and AST-1 in the honeybee brain were monitored via MALDI spectral imaging according to the ontogeny of Africanized Apis mellifera. The levels of these peptides increased in the brains of 0-15 day old honeybees, and this increase was accompanied by an increase in the number of in-hive activities performed by the nurse bees, followed by a decrease in the period from 15 to 25 days of age, in which the workers began to perform activities outside the nest (guarding and foraging). The results obtained in the present investigation suggest that AmTRP-5 acts in the upper region of both pedunculi of young workers, possibly regulating the cell cleaning and brood capping activities. Meanwhile, the localized occurrence of AmTRP-5 and AST-1 in the antennal lobes, subesophageal ganglion, upper region of the medulla, both lobula, and alpha- and beta-lobes of both brain hemispheres in 20 to 25 day old workers suggest that the action of both neuropeptides in these regions may be related to their localized actions in these regions, regulating foraging and guarding activities. Thus, these neuropeptides appear to have some functions in the honeybee brain that are specifically related to the age-related division of labor.
Keywords: MALDI imaging; mass spectrometry; honeybee brain; neuropeptides; ontogeny; proteomics